Communication and Swallowing Difficulties in Geriatric Population - Aayeshah Firdous, Muhammad Sikander Ghayas Khan, Khadija Saleem, Iqra Naseer, Sadaf Hameed, Janet Shanem, Sabahat Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Human life would have had no purpose without the ability of communication. Immense dedication from the side of the teachers, parents and clinical professionals is placed to develop the communication ability in children. The communication of the geriatric demographic however is not paid as much heed as that paid to the pediatric population. This can be proved by the fact that there is unlimited literature readily available to address the communication needs of the children, unfortunately for the elderly, the literature is restricted. Objective: Frequency of the difficulties of communication as well as swallowing were intended to be sighted by the work of the current investigation. Methodology: Exploration of cross section type on the geriatric population that arrived in the tertiary setups, specifically to the Department of Speech and Language Pathology within the district of Lahore, Punjab was administered. Sampling characterized of convenient type to compile particulars and data was executed. Assembly of the details and data was practiced through the use of professional expertise and literature review inspired questionnaire. Analysis of figures and data was accomplished through SPSS 22. Results: 82 (68.9%) males and 37 (31.1%) females, out of 119 participants with Mean age 59.31 ±7.955 years were included in this study. Dysarthria, was the most frequently observed motor disorder of speech. Dysarthria was diagnosed in (42%) meaning 50 individuals. Voice disorder was observed in 16.0% implying 19 had the disorder. 4 Fluency disorder found in 3.4% cases and lastly apraxia was diagnosed in 1.7% of the subjects. Among the disorders of language, subjects were mostly determined to have aphasia. It was found in 33.6% patients equating to 40. Dementia was found in 0.8% of the subjects. 10.9% of the subjects, implying 13 had dysphagia. Practical implication Conclusion: The elderly population concerns with communication and swallowing frequently. The disorder of speech diagnosed most frequently is dysarthria. In language disorders, aphasia was observed more often. Keywords: Apraxia, dysphagia, geriatric, aphasia and dysarthria.